Iron(III) Chelators and Thalassemia - Kumar, Praveen (Asian Journal of Chemistry, 2010)
Despite the known fact that iron is necessary for life, it has its limitations too. The lower or higher concentrations of this metal in the body can be fatal if timely precautions are not undertaken. Transfusional iron-overload is one such type of problem which has affected tens of thousands of patients allover the world. Indians are also not untouched from this deadly disease. Around 10,000 thalassemics are born in the country every year. In this perspective, the present report deals with the introductory information regarding the role of iron chelators in the treatment of thalassemia which is also an iron-overload disease.